Typification and nomenclatural notes on twenty-seven names of Gomphrena L. (Amaranthaceae) linked to the South American flora - Bena, Maria Julia (Phytotaxa, 2017)
Twenty-seven Gomphrena names are here investigated, and discussed. Seventeen names are typified (sixteen lectotypes, one neotype) in the present paper on specimens preserved at B, GOET, M, P, and S, while isolectotypes are found at B, BM, BR, CORD, F, G, M, P, S, and US. Concerning the other ten names, they were previously dicusssed by Holzhammer, who reported the word “Typus”. According to the Art. 7.10 of the ICN Holzhammer’s statements are here interpreted as lectotypifications.